CONSCIENCE AND THE MAGISTERIUM OF THE CHURCH - Gracias, Oswald Cardinal (Asian Horizons, 2016)
Christian life is basically a community life rooted and grounded in Christ. Belonging to God’s family presupposes the responsibility follow the dictates of our conscience formed according to the law of Christ and the moral teachings of the Church. A responsible use of the conscience brings us closer to God. Hence, one must make sure that one has a well formed and informed conscience that is always in search of the truth. In this task, the Church’s moral teaching is essential and to make the Church’s teaching one’s own is a challenge today. The Christian tradition has considered conscience as a gift of God, as a special way of contact between God and human hearts. It has also held the view that though conscience is fallible, its inviolability has to be respected, and that one has the obligation to follow one’s conscience. The dignity and value of the human person depends upon one’s conscience. However, conscience is not an autonomous judge, but derives the criteria for judgment from the eternal, objective moral law. That is, there cannot be an absolute freedom of conscience because the human person is the subject of truth. Based on the theological tradition, especially on the theology of Augustine and Aquinas and Newman, and based on the official documents of the Church, the article explains the understanding and importance of conscience in the Magisterium of the Church.